Terapi Musik terhadap Depresi pada Lansia - Widyastuti, Theresia (Jurnal Ilmiah Psyche, 2019)
Depression is a mood disorder that is generally characterized by hopelessness, excessive helplessness, and lack of enthusiasm for life. Starting from stress that is not overcome, then a person can fall into a phase of depression. This study aims to look at the effect of providing music therapy in reducing depression in the elderly before and after being given a commitment. To achieve this goal, this study uses a quasi-experimental method (Quasi Experiment). The type of research design used is Quasi Experiment with one group pretest and posttest design. The sampling technique was purposive sampling where participants based on population criteria obtained a sample of 16 people. Data collection methods using tests with a scale measuring instrument namely Geriatric Depression Scale (GDS) consisting of 30 item questions, observation methods and interview methods .. Based on data analysis it was concluded that the results obtained were Man Whitney Test U = 0.500 with a value of p = 0.001 ( p <0.01) where the mean ranks on the gain score is 12.44 and the sum of ranks is 99.50, this shows the difference in effectiveness of the effects of music therapy before and after treatment and to test the difference in levels of depression before and after being given music therapy using Wilcoxon Sign Rank test analysis . the results obtained z value = -2.539 with a value of p = 0.11 (p <0.01) so that it can be concluded that there are differences in changes in the level of depression in the elderly before and after given treatment.